Effectiveness of Cold Cabbage Leaf Compress (Brassica Oleracea Var. Capitata) To Reduce Breast Swelling of Breastfeeding Mothers in Purwakarta Regency, Indonesia - Natalia, Widia (HM Publisher, 2024)
Breast engorgement is one of the problems often experienced by breastfeeding mothers. Breast engorgement can cause pain and discomfort and can even inhibit breast milk production. Cold cabbage leaves (Brassica oleracea var. capitata) are a traditional treatment that has long been used to reduce breast swelling. This study aims to determine the effectiveness of cold cabbage leaves in reducing breast swelling in breastfeeding mothers in Purwakarta Regency, Indonesia. This research uses a quasi-experimental design with a pre-post-test approach. The research sample was 60 breastfeeding mothers in Purwakarta Regency, Indonesia. The mothers were divided into two groups, namely the intervention group, who were given cold cabbage leaf compresses, and the control group, who were not given cold cabbage leaf compresses. Breast swelling is measured using the visual analog scale (VAS) pain scale. Measurements were taken on the first day and 7th day after intervention. The results showed that there was a significant difference between the intervention group and the control group in terms of reducing breast swelling. On day 7, the VAS value in the intervention group (3.2 ± 0.5) was lower than the control group (5.5 ± 0.7). Cold cabbage leaf compress is an effective natural way to reduce breast swelling in breastfeeding mothers.